Self-Destructive Symptomatic Frames in Clinical Adolescents: Is the Same Different? - Cruz, Diana (2014)
This study examines individual and family predictors of different self-destructive patterns—only suicidal ideation, only nonsuicidal self-injury (NSSI), or suicide attempts (that may also include both suicide ideation (SI) and NSSI)—in a sample of outpatient adolescents (N = 42; 86% females) with mean age of 16 years (SD = 1.86). Results indicated that there are differences in youngsters with self-destructive behaviors in their perception of paternal rejection and maternal control, when compared with youngsters reporting only SI. Adolescents from the groups with self-destructive behaviors differ only in age. Together, these data highlight the relevance of adopting an ecosystemic perspective, which includes both the patients and their families, regarding treatment and prevention of self-destructive symptomatic frames.